Attitudes Of Muslims Toward Participation In Cash Waqf: Antecedents And Consequences - Intan Fatimah Anwar; Syadiyah Abdul Shukor; Hisham Sabri (Universiti Sains Islam Malaysia, 2024)
Waqf is an act of holding certain property and preserving it for the confined benefit of certain philanthropy that disallows any use or disposition of it outside the specific objective. The Malaysian National Fatwa Council has decided that cash waqf is allowed in Islam. This research aims to investigate Muslim consumer attitude towards participation in cash waqf and implications on their attitude towards participation in cash waqf. This paper reviews literature related to consumer attitude towards participation in cash waqf with the aim to empirically test conceptual model of antecedents and consequences of consumer attitude towards participation in cash waqf. Based on the literature, it is proposed that consumer attitude towards participation in cash waqf is influenced by consumer trust, perceived risk, product knowledge and reference group. Consumer attitude will then lead to consumer intention to participate in cash waqf. This research intends to make contribution to both theory and practice of marketing by providing marketing implications concerning the targeting of cash waqf customers.